2020
DOI: 10.21203/rs.3.rs-98594/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Plasmodium in Domestic Animals in West Sumba and Fakfak, Indonesia

Abstract: Background: Although maximum efforts have been made, malaria in several areas in Indonesia is still high. This study aims to detect the possibility of a Plasmodium reservoir in domestic animals in endemic malaria areas.Methods: Blood from the domestic animal was collected by EDTA tube, smeared and stained by Giemsa for detecting Plasmodium microscopically. Ten µl blood from EDTA tube dripped into filter paper for Plasmodium DNA capture. Nested PCR was used for the molecular detection of parasites, and DNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The current study is a continuation of the findings of h-Plasmodium on previous Etawa goats (1) as an effort to reveal the impasse of information on the role of livestock as hosts for h-Plasmodium. The findings of similar parasites were also reported in livestock populations in Sumba (47). The detected malaria parasites in the trophozoite stage indicated that h-Plasmodium transmission occurred in mammalian livestock groups other than humans.…”
Section: Discussionsupporting
confidence: 81%
“…The current study is a continuation of the findings of h-Plasmodium on previous Etawa goats (1) as an effort to reveal the impasse of information on the role of livestock as hosts for h-Plasmodium. The findings of similar parasites were also reported in livestock populations in Sumba (47). The detected malaria parasites in the trophozoite stage indicated that h-Plasmodium transmission occurred in mammalian livestock groups other than humans.…”
Section: Discussionsupporting
confidence: 81%
“…Specific research on malaria in goats in Indonesia has not been conducted to date. Parasites resembling human Plasmodium in goats in malaria-endemic areas for humans have been reported in West Sumba, Fakfak (Munirah et al, 2020) and Kaligesing (Sumanto et al, 2021). These reports do not specify the possible blood parasite species found based on an approach to P. caprae since they focus on malaria affecting humans.…”
Section: Introductionmentioning
confidence: 99%